Emerging role of IκBζ in inflammation: Emphasis on psoriasis. Issue 10 (17th October 2022) - Gautam, Preeti; Maenner, Sylvain; Cailotto, Frédéric; Reboul, Pascal; Labialle, Stéphane; Jouzeau, Jean‐Yves; Bourgaud, Frédéric; Moulin, David
Abstract: Psoriasis is a chronic inflammatory disorder affecting skin and joints that results from immunological dysfunction such as enhanced IL‐23 induced Th‐17 differentiation. IkappaB‐Zeta (IκBζ) is an atypical transcriptional factor of the IκB protein family since, contrary to the other family members, it positively regulates NF‐κB pathway by being exclusively localized into the nucleus. IκBζ deficiency reduces visible manifestations of experimental psoriasis by diminishing expression of psoriasis‐associated genes. It is thus tempting to consider IκBζ as a potential therapeutic target for psoriasis as well as for other IL23/IL17‐mediated inflammatory diseases. In this review, we will discuss the regulation of expression of NFKBIZ and its protein IκBζ, its downstream targets, its involvement in pathogenesis of multiple disorders with emphasis on psoriasis and evidences supporting that inhibition of IκBζ may be a promising alternative to current therapeutic managements of psoriasis. Abstract : Expression of NFKBIZ is stimulated by cytokines such as IL‐17, TNFα, IL‐1β and IL‐36. Increased expression of IκBζ eventually activates NF‐κB leading to increased expression of various proinflammatory cytokines, chemokines, as well as psoriasis‐associated genes. This cascade of molecules causes recruitment of neutrophils and other immune‐mediated inflammatory cells, which consequently leads to the development of psoriasis‐like skin inflammation.